Optimization of packaging and marketing of Awaina Shrimp Paste as a leading product of Langsa City - Hakim, Sukma Hayati; Sari, Raina Linda; salman,; hanum, nurlaila (Journal of Saintech Transfer, 2025)
Indonesia's coastal resources provide livelihoods for many communities, including Langsa City in Aceh Province, known for its shrimp paste production. Terasi Awaina, a local shrimp paste business, faces challenges with outdated packaging and limited marketing reach. This community service project aimed to optimize Terasi Awaina's packaging and marketing strategies. Conducted over six months, the project involved surveys, practical training, outreach, and mentoring to enhance the business's operations and market appeal. Training focused on modern packaging techniques and establishing an official business website. The results showed significant improvements in participants' knowledge and skills, increased production efficiency, and expanded market reach. Modern packaging and a professional online presence boosted sales and competitiveness. This project demonstrates the potential for technological and digital solutions to drive sustainable development in traditional industries, contributing to economic growth and improved livelihoods in rural communities.